Boosting bulk photovoltaic effect in transition metal dichalcogenide by edge semimetal contact - Shuang Qiao; Jihong Liu; Chengdong Yao; Ni Yang; Fangyuan Zheng; Wanqing Meng; Yi Wan; Philip C. Y. Chow; Dong-Keun Ki; Lijie Zhang; Yumeng Shi; Lain-Jong Li (Light: Science & Applications)
Abstract Oxide materials with a non-centrosymmetric structure exhibit bulk photovoltaic effect (BPVE) but with a low cell efficiency. Over the past few years, relatively larger BPVE coefficients have been reported for two-dimensional (2D) layers and stacks with asymmety-induced spontaneous polarization. Here, we report a crucial breakthrough in boosting the BPVE in 3R-MoS2 by adopting edge contact (EC) geometry using bismuth semimetal electrode. In clear contrast to the typically used top contact (TC) geometry, the EC metal which strongly adheres to the edges and the subtrates can induce a pronounced tensile strain to the 3R-MoS2, and the lateral contact geometry allows to completely access to in-plane polarization from underneath layers reachable by light, leading to >100 times of BPVE enhancement in photocurrent. We further design a 3R-MoS2/WSe2 heterojunction to demonstrate constructive coupling of BPVE with the conventional photovoltaic effect, indicating their potential in photodetectors and photovoltaic devices.